A NEW RECORD OF EUPHORBIACEAE WEEDS FOR PENINSULAR MALAYSIA - Rafidah Abdul Rahman; Nik Faizu Nik Hassan (BRIN Publishing (Penerbit BRIN), 2023)
Caperonia A.St.-Hil. is a new genus record for Peninsular Malaysia, with the species of Caperonia palustris (L.) A.St.-Hil. This paper will provide a description, distribution, habitat, and colour plates of the species.